A new paradigm of hospital care for SARS-COV-2 patients in the post-emergency phase in Italy - Bianchi, F. P.; Cuscianna, E.; Di Lorenzo, A.; Daleno, A.; Mele, F.; Marra, M.; Porfido, R.; Migliore, G.; Tafuri, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
In Italy, at the beginning of the SARS-CoV-2 pandemic, the main organizational model of hospital care was represented by the physical or functional division of hospitals and wards into COVID and non-COVID areas, in order to separate SARS-CoV-2-infected patients from the others. Now that the emergency phase has reached its long-awaited end, it is necessary to develop a new hospital care paradigm that may deal with SARS-CoV-2-positive patients discriminating between those who are hospitalized because of COVID-19 and those who are diagnosed with SARS-CoV-2 infection immediately before or after the first access to healthcare facilities.